Dynamics of β-lactamases in Gram-negative bacteria - Manageiro, Vera (2011)
β-Lactamase production is the most important resistance mechanism among Gram-negative bacteria. The overall aim of this PhD thesis was to contribute to the knowledge of molecular epidemiology of β-lactamases and to the understanding of their diversity in a structural-functional level. To accomplish this aim, several studies with different approaches were performed. The emergence of β-lactamase-producing isolates, as well as the appearance of new epidemic clones, is of great concern. The studies presented in the first chapter of results, have clearly shown that specific extended-spectrum β-lactamase (ESBL)-, plasmid-mediated AmpC β-lactamase (PMAβ)- and carbapenem-hydrolyzing class D β-lactamase (CHDL)-producing clones are able to persist in clinical settings for long periods, resulting in a complex β-lactamase endemic situation. A high diversity of β-lactamases was encountered, specifically: CTX-M family which is the most prevalent ESBL, and PMAβ (e.g., DHA-1, CMY-2, CMY-39, MIR-1, MIR-3, FOX-5 and the novel CMY-46 and CMY-50), both in Enterobacteriaceae, as well as CHDLs OXA-23 and OXA-24/40 in Acinetobacter baumannii. The results obtained in this thesis also highlight different strategies for bacterial spread of resistance that can occur through either clonal spread or horizontal gene transfer of mobile genetic elements. In the second chapter of results, structure/function correlation of five novel clinical important β-lactamases, namely three inhibitor-resistant SHV (SHV-72, SHV-84 and SHV-107), one ESBL (SHV-55) and one parental SHV (SHV-99), are presented. One of the key findings we can infer from results is that the conserved motif Lys234-Thr/Ser235-Gly236, present in class A β-lactamases, is a hot-spot for β-lactamase inhibition, meaning that new compounds can be designed to address this structural feature. In summary, the work performed in this thesis allows the elucidation on the dynamics of β-lactamases in Gram-negative bacteria, in Portugal. Molecular characterization together with biochemical data is essential for understanding the emergence of new resistance mechanisms and their spread.